Pengembangan Aplikasi Kelola Uang Pribadi dengan Bahasa PHP Menggunakan Model RAD - Erwanda, Agil; Erbi, Feriyano; Anwar, Alfian; Septiana, Pendi; Saifudin, Aries; Yulianti, Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Money management for itself for at this moment generation its very difficult to maintain, writer often seen many generation now is consumtion generation, that is why writer starting to develop application money private with php language, with using method RAD (Rapid Application Development), with working focusing every step feature will be seperate to the team, expecting the team will working on this aplication with very fast and appropriate,in developing application web, will be produce a website that can be useful for general public who wants find out how effective this application for public in management money.